Comparison of Phenylephrine, Mephentermine and Ephedrine for Maintenance of Blood Pressure During Subarachnoid Block in Cesarean Section and their Effects on Fetal Outcome - Paudel, Bandana; Paudel, Sumitra; Gautam, Sanjay; Paneru, Monica (Journal of Nobel Medical College, 2025)
Background: Globally, the incidence of hypotension has been very high during cesarean section under spinal anesthesia. Hence, to manage hypotension and maintain adequate blood pressure, vasopressors such as Phenylephrine, Mephentermine, and Ephedrine are commonly used. Materials and Methods: A Prospective Randomized Double-blind study was conducted among 102 singleton pregnant women undergoing cesarean section at Nobel Medical College Teaching Hospital Ltd. Following hypotension, group P received Phenylephrine 100 mcg IV, Group E received Ephedrine 6 mg IV and group M received Mephentermine 6 mg IV. Vital parameters like blood pressure (systolic, diastolic and mean), heart rate, and oxygen saturation were recorded preoperatively as well as intraoperatively. Results: After administering vasopressors, Group P showed a significantly greater increase in blood pressure than Groups E and M at the 4-, 6-, 8-, and 10-minute intervals. However, Group P also demonstrated a significant decrease in heart rate at 4, 6, 16, 18, 20, and 30 minutes compared with Groups E and M. Drug bolus requirements and maternal side effects were similar among groups. Neonatal outcomes were comparable, with Apgar scores >7 in all cases. Conclusion: From our study, it can be concluded that all three vasopressors Phenylephrine, Ephedrine, and Mephentermine were able to restore hypotension during cesarean section, although Phenylephrine achieved faster blood pressure control, though it was associated with a reduction in heart rate. Therefore, phenylephrine is most suitable when rapid blood pressure control is required, provided that heart rate is closely monitored.